The United States balance of payments in 1968 - Brookings Institution; Salant, Walter S.; Council of Economic Advisers (U.S.); United States (Washington : U. S. Govt. Print. Off., 1963)
The study expresses an awareness of changing and possible future patterns. Such as 1. Projection of investment in foreign dollar bonds; 2. Projection of interest and dividend income on investments abroad. 3. Projected increase in "GNP prices" in Europe. 4. Projections of military and other foreign aid expenditures.
Includes index
Includes bibliographic footnotes
usc 09/05/18
Loans
Keywords: Balance of payments